Estudo da utilização de resíduos de construção civil para preenchimento de gabiões caixa - Camelo, Diego Gonçalves (2019)
The series of civil construction data RCC has grown significantly in recent years, with the aim of reducing the work spaces for its emergence in urban areas. Another problematic factor has been the lack of inspection in the discharge of riverbeds, streams and vacant lands, corroborating the spread of diseases through urban vectors. The RCC has been done to challenging administrative administration, because its management is incorrect to the administration of the same temfied made of the environmental impact, social and economic, due to this, the best action mitigator this problem has been a met- is a prime example in the manufacture of new building materials. In view of this, this present research had as objective to analyze the use of the civil construction process in the filling of box gabions. For this purpose, the samples were sampled from construction waste and basalt stone - rachão, for their engineering characteristics; Aging test; Checking the concentration of the tablets by means of ultrasound tests; Simple compression strength and modulus of elasticity. In addition, box gabion cells were filled and filled with RCC and basalt stone - rachão in order to compare and analyze the following tests: Mass measurement to evaluate the specific gravity and to perform the simple compression test. The results were: horizontal and vertical deformations of the gabion filled with the interruption of the civil construction similar to deformations of the conventional gabion for walls up to 5.50m high. However, the resistance to RCC was influenced by the RCC aging test, where performance may influence the technical performance of the gabion. The gabion box filled with Rescue of civil constructive civil construct for the return of RCC to productive cycle of civil construction.